2022
DOI: 10.3390/genes13091537
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: New Players in Cardiomyopathy

Abstract: Cardiomyopathies comprise a heterogeneous group of cardiac diseases identified by myocardium disorders and diminished cardiac function. They often lead to heart failure or heart transplantation and constitute one of the principal causes of morbidity and mortality worldwide. Circular RNAs (circRNAs) are a novel type of noncoding RNAs. They are covalently closed and single-stranded and derived from the exons and introns of genes by alternative splicing. This specific structure renders them resistant to exonuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…The detected circRNAs were considered non-functional or splicing by-products; however, with the development of high-throughput sequencing and bioinformatics approaches, it was found that circRNAs are highly expressed in all eukaryotic cells and perform certain functions [ 35 ]. Recent studies have shown that circRNAs are critical regulators of cell physiology and various pathologies by modulating gene expression [ 29 , 36 , 37 , 38 , 39 ].…”
Section: Characteristics and Functions Of Circrnasmentioning
confidence: 99%
“…The detected circRNAs were considered non-functional or splicing by-products; however, with the development of high-throughput sequencing and bioinformatics approaches, it was found that circRNAs are highly expressed in all eukaryotic cells and perform certain functions [ 35 ]. Recent studies have shown that circRNAs are critical regulators of cell physiology and various pathologies by modulating gene expression [ 29 , 36 , 37 , 38 , 39 ].…”
Section: Characteristics and Functions Of Circrnasmentioning
confidence: 99%